Farmers' Knowledge, Perceptions, and Management PracticesAgainst the Coconut Leaf Beetle (Brontispa Longissima)in Selected Municipalities of Nueva Vizcaya - Tumapang, Jaira Joy (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the socio-demographic characteristics, knowledge, perceptions, and pest management practices of coconut farmers in Bagabag, Quezon, and Kasibu, Nueva Vizcaya, in relation to Coconut Leaf Beetle (Brontispa longissima) infestation. Anchored on the Integrated Pest Management (IPM) framework and farmer behavior perspectives, the research employed a descriptive survey design using a self-constructed questionnaire administered through face-to-face interviews with 60 purposively selected coconut farmers. Data were analyzed using frequency counts, percentages, and weighted mean. Findings revealed that coconut farming is dominated by smallholder, middle-aged farmers with low income and limited educational attainment, factors that constrain access to technical knowledge and adoption of improved practices. A significant knowledge gap exists, with most farmers unfamiliar with the pest and relying primarily on informal information sources. Despite widespread infestation and observable damage, the majority of farmers do not implement pest management practices, while those who do often apply ineffective or non-specific methods. No respondents reported receiving formal training or consulting agricultural experts. However, farmers demonstrated strong awareness of the pest’s importance and expressed high willingness to adopt improved and sustainable management strategies, particularly when provided with training, financial assistance, and technical support. The study concludes that limited access to extension services, training, and resources—rather than lack of motivation—hinders effective pest management. It recommends strengthening agricultural extension programs, promoting IPM and biological control, and providing accessible information and financial support to farmers. This study aligns with Sustainable Development Goals (SDG) 2 (Zero Hunger), SDG 8 (Decent Work and Economic Growth), and SDG 12 (Responsible Consumption and Production) by addressing agricultural productivity, farmer livelihoods, and sustainable pest management practices. Its sustainability impact lies in supporting smallholder resilience, promoting environmentally sound farming practices, and informing institutional and community-level interventions for sustainable agricultural.
Keywords: Coconut Farming; Coconut Leaf Beetle; Farmer Knowledge; Integrated Pest Management; Nueva Vizcaya; Pest Management Practices; Smallholder Farmers